2016
DOI: 10.1111/ene.13117
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral collateral circulation and acute ischaemic stroke

D. Gill

Abstract: Click http://onlinelibrary.wiley.com/doi/10.1111/ene.13111/abstract to view the accompanying paper in this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Collateral circulation refers to the network of blood vessels that contribute towards maintaining blood flow in the absence of the primary conduit [16]. The degree of such collateral blood supply varies amongst individuals and can influence outcomes, especially in patients with AIS due to LVO [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collateral circulation refers to the network of blood vessels that contribute towards maintaining blood flow in the absence of the primary conduit [16]. The degree of such collateral blood supply varies amongst individuals and can influence outcomes, especially in patients with AIS due to LVO [16].…”
Section: Discussionmentioning
confidence: 99%
“…The degree of such collateral blood supply varies amongst individuals and can influence outcomes, especially in patients with AIS due to LVO [16]. Patients with good collateral flow demonstrated less hypoperfused tissue, less infarct growth within the penumbra zone, and smaller infarct volumes with better outcomes than those with poor collaterals [17].…”
Section: Discussionmentioning
confidence: 99%
“…Singer et al [ 38 ] found that the earlier the onset age and the lower the NIHSS score, the better the prognosis of patients. Good CC has also been shown to significantly reduce cerebral infarction volume in patients with symptomatic intracranial atherosclerotic stenosis and lower the risk of cerebral infarction recurrence [ 39 , 40 ]. Besides, the degree of CC opening before illness can affect the clinical prognosis of patients more than that after illness [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stroke represents the largest proportion of papers published, including those on pathophysiology , acute stroke management and the outcome of patients who have suffered stroke . Stroke is a worldwide problem, but its prevalence varies and may reflect both the genetic and environmental contributions to stroke, both in turn reflecting the known risk factors for stroke.…”
mentioning
confidence: 99%